Empowering MSMEs through Visual and Digital Transformation: Strengthening Branding and Technology-Based Market Access - Sholikha, Nikmatus; Nurdiansyah, Rudi; Alhafidh, Muhammad Nursyamsu; Hamas, Ryan Wajdy; Alfarisyi, Ri’syad Salman; Toyyibah, Corin Saila Rizqi (Jurnal Pengabdian Masyarakat Bhinneka, 2025)
Digital transformation has become a key foundation for the development of micro, small, and medium enterprises (MSMEs) in Indonesia, expanding market access and improving business efficiency. However, many MSMEs—especially those in the micro-scale batik handicraft sector—still face obstacles in digital adaptation, such as low technological literacy, limited infrastructure, and a lack of relevant branding strategies. This community service activity aims to empower MSMEs through visual and digital transformation to strengthen their brand image (branding) and expand technology-based market access. The approach used includes digital literacy training, visual rebranding assistance, website-based company profile creation, and marketing optimization through marketplaces and social media. Furthermore, artificial intelligence (AI) technology was applied to efficiently create visual promotional content. The activity results showed an increase in participants' abilities in visual identity management, brand narrative development, and digital platform utilization. Partner MSMEs experienced increased market reach and brand professionalism, and were able to integrate digital marketing processes with promotional cost efficiencies of up to 40%. This activity demonstrates that visual and digital transformation plays a significant role in strengthening the sustainability and competitiveness of local MSMEs in the technology-driven economy.